(untitled) (Journal of the College of Education for Women, 2020)
The aim of this research is to study the modern Spanish writings on the biography of Prophet Mohamed (PBUH), which gave the glorious biography its due by objective study and analysis with a scholarly approach, unlike the old Spanish and European oriental writings with its biased approach. In the past, Spanish and European writings on Prophet Mohamed were influenced by religious extremism and did not do any justiceto Prophet Mohamed. But this has changed in the modern times, and modern writing on the Prophet biography is based on objective analysis and reliance on original sources instead of the sources of the churches which were full of hate and wicked intentions to eliminate Islam.The research came to the conclusion that the modern Spanish writings were liberated from the influence of the church and its control on thinking, although there are still some voices that are motivated by hate of Islam. But the voices of hate are weak against the louder ones that show unbiased approach in research that became clear in the twentieth century.The research recommends that the attention should be given to the fair Muslim and non-Muslim orientalist researchers, whether in Spain or other European countries and shed the light on their writings that reject the biased and unjust opinions on Prophet Mohamed by publishing their books and inviting them to attend conferences and events held in Arab and Muslim countries. This will be a significant factor in spreading Islam in Western countries.